The Trope of Africanism to Address Homosexuality in Giovanni’s Room by James Baldwin - Francesca Scaccia (JAm It!, 2024)
In the preamble to the Declaration of Independence “Life, Liberty, and the Pursuit of Happiness” are described as being unalienable rights of people and moreover, they constitute the core of the American national ethos: ‘the American Dream’. Nevertheless, full access to the plenty of potentialities inherent in this rhetoric seems to have been denied to specific categories of people, thus resulting in an endorsement of exclusivity and discrimination, when actually it should have supported inclusivity and equal opportunities to every American citizen. Especially the notion of “liberty” has historically been influenced by many socially constructed categories in the US, notably race, religious belief, gender, and sexual orientation. Therefore, the connected conceits of ‘life’ and ‘the pursuit of happiness’ couldn’t help but be reshaped by those categorizations. This despicable state of things had such a profound impact on the life and works of many authors – especially on those who closely faced an unjust set of domination and discrimination due to their ethnicity and sexuality that they publicly condemned how suffocating and hypocritical American society still was in the twentieth century. Among them stands the influential African American writer James Baldwin, a figure in which one can really feel the struggle of being labelled as both African American and homosexual by the hypochondriac white society of the US. In his second novel entitled Giovanni’s Room (1956), Baldwin deeply explored the theme of the ‘quest for self-identity’ in connection with the theme of sexual orientation. Thus, the aim of this paper is to investigate how – and why – Baldwin makes use of Africanist, or Africanlike, characters (e.g., the Italian immigrant Giovanni) to explore topics that otherwise would have been taboo, which means homosexuality and even bisexuality in the American society of the 1950s. In particular, the analysis will rely on the seminal work of literary criticism Playing in the Dark: Whiteness and the Literary Imagination (1992), by Toni Morrison, who greatly examined the peculiar use of black characters in American literature for the first time.